The Development of Web-based Sales and Inventory System for a Stationary Store - Utami, Chyntia Cahya; Desanti, Ririn Ikana; Halim, Fransiscus Ati (ULTIMA InfoSys, 2023)
The study-case method was applied in this research at a stationery store. The problems derive from an observation of a stationary store called Andesta, a micro, small, and medium-sized enterprise (MSMEs) run by individuals who engage in stationery and document procurement. The problem is that transactions are not properly recorded, preventing the store from knowing the profits and losses incurred during a certain period. As a result, the availability of stocks coming in and out is unclear. This issue will be resolved by developing an integrated sales and inventory system. The prototype method is implemented in the system development lifecycle. The system will be constructed as soon as the design is completed and accepted by the business owner. The CodeIgniter framework and MySQL databases were used to build the system. The construction of the sales and inventory system is supposed to support stores in running their business processes more efficiently.